Fire resistance in a population of Cyathea atrovirens (Langsd. & Fisch.) Domin (Cyatheaceae) in the state of Rio Grande do Sul, Brazil. - Caroline Leuchtenberger; Carlos Rodrigo Lehn (Biotemas, 2008)
Cyathea atrovirens (Langsd. & Fisch.) Domin is a tree fern that occurs in the state of Rio Grande do Sul from sea level to an altitude of 300m. We monitored a population of 10 individuals of C. atrovirens affected by burning in the municipality of Campo Bom, Rio Grande do Sul, Brazil. The objective of this study was to analyze the responses of a Cyathea atrovirens population after the occurrence of a fire, considering the following aspects: frond production, annual rates of relative growth of caudex length, and the production, maturation and release of spores. The sporophytes of larger size produced more fronds than the smaller ones. We observed a significant relationship between caudex length and relative growth (TCR) in individuals of smaller size. In the first year, after the fire, all individuals produced new fronds. The spore production was asynchronic. The species apparently demonstrated its capacity to support the occurrence of quick fires, since the post-fire frond production was gradually reestablished.